Dinamika Resiliensi Mahasiswa Semester Akhir Program Studi Bimbingan dan Konseling Universitas Negeri Surabaya - Abellita Putri Dika Ramadhani; Denok Setiawati (SENTRI: Jurnal Riset Ilmiah, 2026)
The last grade students are under much pressure academically and psychologically when completing their final undergraduate project, which may affect their psychological happiness and impede the continuation of their academic. Under these circumstances, students need to build resilience so they can respond positively and succeed in their studies despite many difficulties. Previous studies on student resilience have largely focused on general resilience outcomes or treated resilience as a relatively stable personal characteristic. The purpose of this study is to discover how resilience manifests in the dynamic process among final-year university students in the Guidance and Counseling Program at Universitas Negeri Surabaya. For this research, a qualitative descriptive design was used following a purposive selection of five final year students. Personal experiences of students in coping with academic pressure, emotional disturbance, and adaptive strategies in the process of thesis writing were included by means of interviews. Thematic analysis was done, and patterns in the data were sought concerning factors towards resilience. Results suggest that student resilience is dynamic and evolves through ongoing internal-external transactions. This finding extends existing resilience studies by highlighting the fluctuating and situational nature of resilience during the thesis completion phase. The most difficult parts seem to be emotional regulation and impulse control during times of academic insecurity. But hope, social support, and self-efficacy were instrumental in their resilience in the face of high academic pressure. Over time, students derived positive meaning from their hardships, which facilitated the development of adaptive capacity. These results indicate that resilience in final year students is not the lack of stress, but to develop adequate emotional responses in order to address academic difficulties. The findings also underscore the significance of guidance and counseling services in higher education for promoting emotional regulation, self-efficacy, and resilience development in students’ academic performance.